Molecular characterization of colletotrichum isolates associated with anthracnose of mango fruit - Latiffah Zakaria,; Nurul Zaadah Juhari,; Suzianti Iskandar Vijaya,; Intan Sakinah Mohd Anuar, (Universiti Kebangsaan Malaysia, 2015)
Colletotrichum species are well-known causal agent of anthracnose. A study was conducted to determine the identity of Colletotrichum associated with anthracnose of mango (Mangifera indica) fruits. Thirty five Colletotrichum isolates were isolated from anthracnose lesion of two mango cultivars, Chokanan and Harum Manis. Based on the conidial morphology, two morphotypes (I and II) of C. gleosporioides were identified. Based on BLAST search of ITS regions and β-tubulin sequences, majority of the isolates showed 99-100% similarity with Colletotrichum sp. from mango and other hosts and three isolates, 100% similarity with C. asianum. From phylogenetic analysis using maximum likelihood method of combined datasets, the isolates from mango formed three clades, which corresponded to C. gloeosporioides sensu lato and C. asianum. Therefore, the present study showed that the isolates associated with anthracnose of mango belong to C. gleosporioides sensu lato and C. asianum.